Leadership in the face of digital transformation in an Ecuadorian manufacturing company in 2020 - Ortíz Maldonado, Carlos Alberto; Castillo Quintana, María Belén (Journal of business and entrepreneurial studie, 2022)
The present research focused on determining the predominant leadership style in the productive areas of an Ecuadorian manufacturing company, and the level of digital transformation during the year 2020. The study was developed through cross-sectional descriptive research. The multifactorial leadership questionnaire and key performance indicators were used as instruments, which were applied digitally using Google forms. The population studied was 151 workers and the sampling technique was probabilistic. The results allowed determining that 74% of the transformational leadership guidelines are practiced, 77% of transactional leadership and 9% of laissez-faire. The level of digital transformation had an increase of 19% in the fourth quarter compared to the first quarter of the year, evidencing in practice the implementation of automation mechanisms, use of digital media and documents and implementation of technology. It was concluded throughnthe literature and theoretical review that to face the technological advance, the transformation leadership style with all its dimensions is the most appropriate because it promotes development, innovation and knowledge management